The principle of fair play in education of football fans - Kowalska, Jolanta Elżbieta (Journal of Education, Health and Sport, 2019)
In this study, an attempt has been made to characterize football fans in the context of the possibility of counteracting undesirable behaviour of audiences by sport education and promotion of the principle of fair play. It was assumed that this idea, as a universal value in sport and life, is understandable to all people and widely accepted.